Prognosis after mastectomy versus repeat lumpectomy in patients with ipsilateral breast cancer recurrence: A propensity score analysis. Issue 4 (April 2016) - Yoshida, A.; Takahashi, O.; Okumura, Y.; Arima, N.; Nakatsukasa, K.; Tanabe, M.; Shien, T.; Masuda, N.; Tanaka, S.; Komoike, Y.; Taguchi, T.; Iwase, T.; et al.
Abstract: Introduction: Mastectomy is the current standard surgical procedure for ipsilateral breast tumor recurrence (IBTR). However, there is little evidence about the prognostic impact of the surgical procedure (mastectomy versus repeat lumpectomy) for IBTR. Patients and methods: A total of 271 consecutive patients who had histologically confirmed IBTR without distant metastases and underwent definitive surgery for IBTR between 1989 and 2008 were included from eight institutions in Japan. The impact of the surgical procedure for IBTR on distant disease-free survival (DDFS) and overall survival (OS) was evaluated using and multivariable proportional hazards regression and propensity score matching methods. Results: Of the 271 patients, 149 patients (55%) underwent repeat lumpectomy and 122 patients (45%) underwent mastectomy after IBTR. The median follow-up period from definitive surgery for IBTR was 55 months. There was no difference in terms of DDFS and OS between repeat lumpectomy and mastectomy after IBTR, adjusted for various clinical and tumor characteristics. In addition, for the matched patient cohort, no difference in DDFS and OS was seen between the 2 groups. Conclusion: In our study, both multivariate analysis and the propensity score matching method demonstrated that there was no difference in terms of DDFS and OS between repeat lumpectomy and mastectomy after IBTR. Further studies are warranted (UMIN-CTR number UMIN000008136).